Killing Christians : living the faith where it's not safe to believe - Doyle, Tom, 1955--; Webster, Greg (Nashville, Tenn : W. Pub. Group, 2015)
"The depth of oppression Jesus followers suffer is unimaginable to most Western Christians, yet it is an everyday reality for those who choose faith over survival in Syria, Iran, Egypt, Lebanon, and other countries hostile to the Gospel of Christ. Doyle takes readers to the secret meetings, the torture rooms, the grim prisons, and even the executions that are the "calling" of countless Muslims-turned"--Provided by publisher.
Keywords: Christian converts from Islam -- Biography; Missions to Muslims; Islam -- Relations -- Christianity; Christianity and other religions -- Islam